The modified iterative algorithm for localization in sensor networks - Jiang, Bin (2016 IEEE International Conference on Electronic Information and Communication Technology (ICEICT), 2016)
Low-cost and accurate sensor localization estimation is an imperious requirement for the deployment of wireless sensor networks (WSNs) in a wide variety of applications. Multidimensional Scaling (MDS), one class of localization technique has been applied to location estimation and topology discovery. In case of large measurement errors, using Iterative Multidimensional Scaling (IT-MDS) can't get enough accurate relative position estimates of nodes. In this paper, we devise a modified iterative scheme for sensor location estimation. Then we propose several MDS algorithms and compare their effects on the accuracy of localization with our algorithm. Simulation experiments show the results of modified Iterative Multidimensional Scaling algorithm are more precise than others at the same condition.